Analisis Ekonomi Politik dalam Penanganan Ketimpangan Ekonomi di Indonesia - Adrian Kurnia Sobana Putra; Yusuf Vedi Velandi; Rangga Rangga (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Political economic analysis in handling economic inequality in Indonesia reveals that although the Gini Ratio shows a decline, economic inequality remains a serious issue. Inequality is seen from the uneven distribution of income, access to education, and economic opportunities. The purpose of this study is to analyze the role of political economy in handling economic inequality and to open up policies that have been implemented in Indonesia. The research method used is qualitative research with a descriptive analytical approach. The government has launched various policies such as social assistance and infrastructure development, but implementation challenges such as resources, corruption, and lack of coordination between institutions still hamper the effectiveness of these policies.